Tetrachlorinated Tetraazaperopyrenes (TAPPs): highly fluorescent dyes and semiconductors for air-stable organic n-channel transistors and complementary circuits - Martens-Kruck, Susanne; Wadepohl, Hubert; Gade, Lutz H. (Chemistry - a European journal, 2012)
A range of 2,9-perfluoroalkyl-substituted tetraazaperopyrene (TAPP) derivatives (1-5) was synthesised by reacting 4,9-diamino-3,10-perylenequinone diimine (DPDI) with the corresponding carboxylic acid chloride or anhydride in the presence of a base. The reaction of compounds 1-4 with dichloroisocyanuric acid (DIC) in concentrated sulphuric acid resulted in the fourfold substitution of the tetraazaperopyrene core, yielding the 2,9-bisperfluoroalkyl-4,7,11,14-tetrachloro-1,3,8,10-tetraazaperopyrenes 6-9, respectively. The optical and electrochemical data demonstrate the drastic influence of the core substitution on the properties. All compounds are highly luminescent (fluorescence quantum yields of up to Φ=0.8). The LUMO energies of the tetrachlorinated TAPP derivatives (determined by cyclic voltammetry and computed by DFT calulations) were found to be below −4 eV. In the course of this work the performance of TAPP derivatives in organic thin-film transistors (TFTs) was investigated, and their n-channel characteristics with field-effect mobilities of up to 0.14 cm2 V−1 s−1 and an on/off current ratio of >106 were confirmed. Long-term stabilities of 3-4 months under ambient conditions of the devices were established. Complementary inverters and ring oscillators with n-channel TFTs based on compound 8 and p-channel TFTs based on dinaphtho-[2,3-b:2′,3′-f]thieno[3,2-b]thiophene (DNTT) were fabricated on a glass substrate.